2022
DOI: 10.1039/d1nj05658a
|View full text |Cite
|
Sign up to set email alerts
|

Current research progress on laccase-like nanomaterials

Abstract: Natural laccase exhibits a broad substrate and only water is a by-product, making it an environmentally friendly enzyme. It has good application prospects in food engineering, paper making, textile, environmental...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…30,34 It is reported that Cu 2+ alone can slowly catalyze the reaction of 2,4-DP with 4-AP and induce a light pink of the reaction solution, exhibiting a weak catalytic activity. 35 However, the significantly stronger PPO-like activity is derived from CuNAD instead of from free Cu 2+ or others (Figure S8). In addition, compared with the free Cu 2+ , the amount of exposed copper sites of CuNAD is decreased after coordination, confirming that the activity of copper greatly improved after coordinating with NAD + .…”
Section: Catalytic Performance Of Cunad For Polyphenolmentioning
confidence: 99%
“…30,34 It is reported that Cu 2+ alone can slowly catalyze the reaction of 2,4-DP with 4-AP and induce a light pink of the reaction solution, exhibiting a weak catalytic activity. 35 However, the significantly stronger PPO-like activity is derived from CuNAD instead of from free Cu 2+ or others (Figure S8). In addition, compared with the free Cu 2+ , the amount of exposed copper sites of CuNAD is decreased after coordination, confirming that the activity of copper greatly improved after coordinating with NAD + .…”
Section: Catalytic Performance Of Cunad For Polyphenolmentioning
confidence: 99%
“…Since scientists discovered the first kind of inorganic nanometer material Fe 3 O 4 with catalytic activity, thorough research began to be carried out for other nanometer materials. Some of them show similar catalytic activities to natural enzymes, and the catalytic reactions conform to the basic kinetic principles and mechanisms of enzymes, which are called nanozymes. Compared to natural enzymes, they exhibit similar catalytic activity, simple preparation, and stable properties, thus show promising applications in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inherent lack of fine structure in nanozymes leads to low specificity for targeted substrates, , which fails to replace natural enzymes completely in practical applications, especially in the analysis and detection of specific substances. For example, natural polyphenol oxidase is often used to quantify phenols, which play an important role in human life. , While most of the explored oxidase nanozymes lack enzyme-like selectivity, they generally catalyze the substrate oxidation by activating O 2 to produce reactive oxygen species. Thus, they can not only oxidize phenolic compounds but also catalyze a series of reducing substrates containing 2,2′-azino-bis­(3-ethylbenzothiazoline-6-sulfonic acid)-diammonium salt (ABTS), 3,3′,5,5′-tetramethylbenzidine (TMB), o -phenylenediamine (OPD), and glutathione.…”
Section: Introductionmentioning
confidence: 99%